Improving Patient Flow in the Emergency Rooms using Coloured Petri Nets and the ACO Algorithm - Louhab, Zouaoui; Boufera, Fatma (Journal of Soft Computing Paradigm, 2024)
Overcrowding is certainly one of the major problems that have affected the work of the health care system in recent years, especially in the Emergency Department (ED), In addition, overcrowding has a significant impact on the quality of health care in hospitals. In addition to creating issues for patients and staff, overcrowding in the ED can lead to medical errors, longer wait times, and thus causes financial losses to hospitals. Emergency services are considered necessary in society, given the human need for them at any stage of their life. The emergency department is a complex system due to the nature of the resources it contains. Many researchers are interested in proposing many solutions to solve many problems in the emergency department. Researchers rely on many methods and techniques such as simulation, optimization algorithms, data mining, and other methods. In this research, we try to propose an approach based on the ant colony optimization (ACO) algorithms and colored Petri nets, the aim of which is to reduce waiting times and thus reduce the length of the patient’s stay. Simulation models are built utilizing colored Petri nets, and to determine human resources, the ACO algorithms are used. This research helps the administrative staff in the emergency department find appropriate solutions for human resources.
Keywords: Emergency department; Coloured Petri Net; ACO; simulation; optimization